GEOCHEMICAL CHARACTERISTICS OF KARAMAILI OPHIOLITE IN EAST JUNGGAR, XINGJIANG: PRODUCTS OF RIDGE SUBDUCTION - Liu X.J.; Xu J.F.; Bai Z.H.; Hou Q.Y.; Lei M. (My University, 2007)
The mafic rocks of Karamaili ophiolite in East Junggar of Xinjiang province show both compositional characteristics of a mid-ocean ridge basalt(MORB) and an island-arc basalt (IAB). They display flat to light rare earth element (REE)-depleted and slight enriched patterns. The spider diagrams for trace elements indicate that they are variable depleted in high filed-strength elements (HFSE), but enriched in large ion lithophile elements(LILE). The composition characters of these mafic rocks are much similar to those of the Chile Ridge and Cocos Ridge basalts, which are typically affected by ridge subduction. Discrimination diagrams demonstrate that mafic rocks of the Karamaili ophiolite plot within the arc and MORB filed, and show a transitional composition from IAB to MORB, therefore the ophiolite was possibly formed in a subducted ridge-affected island arc or forearc setting. Relatively high εNd(t) values (7.2 ∼ 9.8) and low Nb /Zr,Ta/Yb ratios suggest that at least three components were involved in their source: sub-arc depleted mantle; fluids dehydrated from the subducted slab and marine sediment and MORB mantle.
Keywords: ARC ISLAND; JUNGGAR; KARAMAILI; OPHIOLITE; RIDGE SUBDUCTION